Epithelioid Trophoblastic Tumor—A Challenge to Manage due to Its Rare Existence: A Case Report with Review of Literature - Neetha Nandan; Vijith Shetty; Roopali Chaturvedi (Indian Journal of Medical and Paediatric Oncology)
Epithelioid trophoblastic tumor (ETT) is the rarest type of gestational trophoblastic neoplasia. It has variable presentations and is an aggressive tumor. Because of its rarity, it is difficult to establish an appropriate diagnosis, management, and follow-up. A woman of age 45 years postmenopausal status with an antecedent term pregnancy 13 years back was diagnosed to have ETT in the hysterectomy specimen. She had come with urinary retention as the tumor was infiltrating the bladder. Beta-human chorionic gonadotropin levels were normal. Immunohistochemistry confirmed the diagnosis. Though metastatic workup was normal, adjuvant multiagent chemotherapy was given as the bladder flap margin was not free of tumor cells and antecedent pregnancy was > 4 years. Every new case of ETT needs to be reported to bring about more awareness of the unusual presentations, and it may help come to a consensus for appropriate management.